Comparative analysis between biofilm formation and gene expression in Staphylococcus epidermidis isolates - Freitas, Ana Isabel (2018)
Aim: To understand the relationship between ica, aap and bhp gene expression and the implications in biofilm formation in selected clinical and commensal Staphylococcus epidermidis isolates. Material & methods: Isolates were analyzed regarding their biofilm-forming capacity, biochemical matrix composition, biofilm spatial organization and expression of biofilm-related genes. Results: On polysaccharide intercellular adhesin-dependent biofilms, aap and bhp contributions for the biofilm growth were negligible, despite very high levels of expression. In contrast, smaller increases in icaA expression contributed significantly to biofilm growth. Interestingly, no biological differences were observed between clinical and commensal strains. Conclusion: These results reinforce the concept that S. epidermidis is an 'accidental pathogen,' and that the ica operon is the main mechanism of biofilm formation in clinical and commensal isolates. © 2018 Future Medicine Ltd.